A Proposal for a Simulation of PCAD Network Topology Using SimGrid - Matos, Rayan Raddatz de; Schnorr, Lucas Mello (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS), 2026)
Simulation is a well-established methodology for evaluating High-Performance Computing (HPC) systems, ensuring reproducibility and reduced energy footprints. This work proposes a programmatic network model of the PCAD infrastructure, a heterogeneous institutional cluster, using the SimGrid S4U API. Focusing on four core partitions, we map the physical architecture into a simulated structure and calibrate the platform properties with experimentation. The main goal is to enable local researchers to replicate experiments and study scalability even with limited physical hardware.